Film Studies in Peru: a systematic review - Nuñez-Alberca, Alejandro (2025)
Peruvian film production has witnessed a multiplicity of proposals and new voices since the turning of the century, but the academic production of Film Studies continues to lack a comprehensive review of what is being studied, who is doing the research, where it is being conducted, and where these works can be read. This paper aimed to identify the main characteristics of the field of Film Studies in Peru between 2016 and 2023. Using a quantitative approach, a systematic literature review was conducted based on the PRISMA 2020 protocol, with Scopus and Web of Science databases as references. The data of the registers was processed through bibliometric indicators. The final sample consisted of 46 records that met the selection criteria. The results point to a considerable increase in film studies since the mid-2010s, as well as emerging research trends inspired by Humanities such as aesthetics, literature, and philosophy. There is also a sustained interest in exploring relatively recent national cinemas, alongside the study of films and directors from other countries. Finally, the revision concludes by identifying the strengths and challenges faced by Film Studies scholars in Peru, such as the need to articulate the researchers in networks and have specialized programs and events in academic environments.